Penguatan Kapasitas Organisasi Perangkat Daerah melalui Sosialisasi Indeks Pembangunan Keluarga di Kota Samarinda - Anif Muchlasin (AKSIOLOGI: Journal of Community Development, 2025)
The socialization of the Family Development Index (iBangga) in Samarinda City is part of a community service program with a descriptive-participatory approach, which aims to increase the understanding of local stakeholders regarding the importance of family development as the basis for human development. The activity was carried out by the Population Control and Family Planning Agency (DPPKB) of Samarinda City on September 25, 2025, at the DPPKB Office Hall in Samarinda City, involving 50 participants consisting of village heads, sub-district heads, Family Planning Assistant Cadres (PPKB), and Family Planning Field Officers (PLKB) from all sub-districts in Samarinda City. The activity was evaluated through pre-tests and post-tests to measure the increase in participants' knowledge of the concept and application of iBangga. The analysis results showed an increase in the average score from 61.28 on the pre-test to 64.47 on the post-test, with the median increasing from 60 to 65. The distribution of participants' scores also shifted towards higher scores, indicating that the socialization had a positive impact on participants' understanding. Enthusiasm was evident from the many questions asked, particularly regarding budgeting, technical measurement of iBangga indicators, concrete steps for implementation at the sub-district and village head levels, and strengthening the role of cadres in the field. The results of this activity have practical implications for regional policy, namely the importance of drafting a Mayor Regulation (Perwali) on the Implementation of iBangga in Samarinda City as a legal umbrella that strengthens governance and reporting on family development. In addition, sustainable budget support, capacity building for officials and cadres, and the use of iBangga data in evidence-based family development planning at the village and sub-district levels are needed.